Altered gene expression of glycosyltransferases and sialyltransferases and total amount of glycosphingolipids following herpes simplex virus infection. (3rd November 2016) - Miyaji, Kazuki; Furukawa, Jun-ichi; Suzuki, Youichi; Yamamoto, Naoki; Shinohara, Yasuro; Yuki, Nobuhiro
Abstract: There is a case report of a patient with overlapping Guillain–Barré syndrome and Bickerstaff brainstem encephalitis after infection with herpes simplex virus type 1 (HSV-1), who carried high titers of serum anti-GQ1b IgG antibodies. Several studies have linked viral infection to the modulation of ganglioside expression such as human T-lymphotropic virus to GD2 and simian virus 40 to GM3. Also, enhancement of the expression of GM2 on the cell membrane after cytomegalovirus infection has been reported. The objective of this study was to unveil the relationship between HSV-1 infection and the alteration of cellular ganglioside expression in neuronal and glial cell lines. In addition to these cell lines, several human tumor cell lines including astrocytoma cells, neuroblastoma cells, T-cell leukemia cells and kidney cells derived from normal human and monkey were infected with HSV-1 as well as HSV-2. To measure changes in ganglioside-related gene expressions and gangliosides levels in cells, quantitative PCR and glycosphingolipid-glycomic analysis were performed. Changes in gene expression of glycosyltransferases and sialyltransferases were observed in HSV-1- and HSV-2-infected cells, although with different trends. 39 glycosphingolipid-glycans were quantitatively analyzed. HSV-1 and HSV-2 infections resulted in changes in the total amount of gangliosides depending on the cell lines used and type of virus. Qualitative changes caused by each infection of HSV-1 and HSV-2 were almost negligible. Graphical abstract: Highlights: Gene expression changes were observed in HSV-1-infected neuronal and glial cell lines. HSV-1 infections resulted in changes in the total amount of gangliosides. Qualitative changes caused by each infection of HSV-1 were almost negligible.